2022
DOI: 10.1038/s41467-022-30914-3
|View full text |Cite
|
Sign up to set email alerts
|

Viral coinfection promotes tuberculosis immunopathogenesis by type I IFN signaling-dependent impediment of Th1 cell pulmonary influx

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), is often exacerbated upon coinfection, but the underlying immunological mechanisms remain unclear. Here, to elucidate these mechanisms, we use an Mtb and lymphocytic choriomeningitis virus coinfection model. Viral coinfection significantly suppresses Mtb-specific IFN-γ production, with elevated bacterial loads and hyperinflammation in the lungs. Type I IFN signaling blockade rescues the Mtb-specific IFN-γ response and ameliorates lung immunopatholo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Sp140 −/− mice are a unique mouse model of the aberrant type I IFN response, as they do not require repeated administration of TLR agonists, viral co-infection, or other perturbations of the innate immune system for type I IFN production (Antonelli et al, 2010; Kang et al, 2022; Mayer-Barber et al, 2014; Moreira-Teixeira et al, 2020; Redford et al, 2014). Other groups have also modeled the type I IFN response by infecting B6 mice with a lineage 2 clinical Mtb strain, like HN878 (Akter et al, 2022; Manca et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sp140 −/− mice are a unique mouse model of the aberrant type I IFN response, as they do not require repeated administration of TLR agonists, viral co-infection, or other perturbations of the innate immune system for type I IFN production (Antonelli et al, 2010; Kang et al, 2022; Mayer-Barber et al, 2014; Moreira-Teixeira et al, 2020; Redford et al, 2014). Other groups have also modeled the type I IFN response by infecting B6 mice with a lineage 2 clinical Mtb strain, like HN878 (Akter et al, 2022; Manca et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Mice are able to model the viral induced loss of Mtb control seen in humans, with chronic lymphocytic choriomeningitis virus (LCMV), acute LCMV, pneumonia virus of mice, and influenza A virus co-infection with Mtb all exacerbating tuberculosis disease (Kang et al, 2022; Redford et al, 2014; Volkert et al, 1947; Xu et al, 2021). Additionally, virus-induced type I IFN drove the loss of Mtb control during the acute LCMV and influenza co-infections (Kang et al, 2022; Redford et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lineage 2 strains such as Mtb HN878 induces higher concentration of IFNa/b than the commonly used laboratory strains, and the virulence mechanism is linked to IFN-I-mediated impairment of Th1 immune response 39 . IFN-I has been shown to inhibit T-cell proliferation in vitro 66 and delays Th1 response in the lung in a mouse model of LCMV-Mtb coinfection 67 . Here we showed that IFN-I inhibition in Mtb infected susceptible mice curtails neutrophil influx, augments T-cell proliferation, and most importantly improved the disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…To perfuse the lungs, cold PBS containing heparin was injected into the heart until the lungs appeared white. Then, single-cell suspension of the lung and spleen was prepared as previously described ( 23 ). For phenotypic analysis of lymphocytes, single-cell suspensions were stained with the following Abs; BD Biosciences (San Jose, CA, USA): anti-CD4 (RM4-5)-PerCP-Cy5.5, anti-CD8a(53-6.7)-FITC; eBioscience (San Diego, CA, USA): anti-CD8a(53-6.7)-PerCPCy5.5; Biolegend (San Diego, CA, USA): anti-CD4(RM4-5)-BV605.…”
Section: Methodsmentioning
confidence: 99%